Phylogeography of Syringa josikaea (Oleaceae): Early Pleistocene divergence from East Asian relatives and survival in small populations in the Carpathians. (23rd March 2015) - Lendvay, Bertalan; Kadereit, Joachim W.; Westberg, Erik; Cornejo, Carolina; Pedryc, Andrzej; Höhn, Mária
Abstract : Tertiary relict plant species of Europe have had a large distribution range before the Pleistocene but today are confined to small refugial areas. Syringa josikaea of the largely East Asian genus Syringa is a shrub of temperate forests in the Carpathians, restricted to altogether 25 small populations in two disjunct areas, the Apuseni Mountains (Romania) and the Ukrainian Carpathians. Miocene and Pleistocene fossil remains indicate the long‐term presence of the species in Central Europe; hence S. josikaea has been considered a Tertiary relict. We aimed at clarifying the historical biogeography of S. josikaea by estimating the divergence time between S. josikaea and its Asian relatives, and by analysing intraspecific variation using multiple DNA sequences as well as microsatellites. The estimated divergence time between S. josikaea and its closest relatives based on nuclear ribosomal DNA sequences is 1.88 Mya [0.30–4.04 Mya highest posterior density], suggesting a relatively recent disruption of a formerly continuous distribution area. This time corresponds to the period of Early Pleistocene extinctions, when many Tertiary plant taxa went extinct in Europe. Sequence variation was found to be very low within S. josikaea . Complete identity among all samples in cpDNA may imply a bottleneck. Four different ribotypes found showed no geographic differentiation between the Apuseni Mountains and the Ukrainian Carpathians, and differentiation between these two areas was weak when considering microsatellite variation. Together these observations may imply that the extant disjunct distribution of the species arose only recently, either through colonization from one glacial refugial area or from disruption of one such area. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.